2020
DOI: 10.2139/ssrn.3651864
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Risk in Financial Networks: A Survey

Abstract: We provide an overview of the relationship between financial networks and systemic risk. We present a taxonomy of different types of systemic risk, differentiating between direct externalities between financial organizations (e.g., defaults, correlated portfolios and firesales), and perceptions and feedback effects (e.g., bank runs, credit freezes). We also discuss optimal regulation and bailouts, measurements of systemic risk and financial centrality, choices by banks' regarding their portfolios and partnersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 164 publications
(210 reference statements)
0
6
0
Order By: Relevance
“…The SEC's Associate Director of Trading and Markets, Michael Macchiaroli (2009) emphasized that "the Commission did not relax any requirements at the holding company level because previously there had been no requirements." 2 The extreme leverage of the five investment banks, the existential crises faced by all of them in 2008, and the big post-crisis drop in leverage of the two survivors (Goldman Sachs and Morgan Stanley), all support a view that the SEC had not supervised the investment banks (or their subsidiaries) adequately from the viewpoint of solvency. The Inspector General of the Securities and Exchange Commission (2008) found that the SEC's Division of Trading and Markets "became aware of numerous potential red flags prior to Bear Stearns' collapse [in March 2007], regarding its concentration of mortgage securities, high leverage, shortcomings of risk management in mortgage-backed securities and lack of compliance with the spirit of certain Basel II standards, but did not take actions to limit these risk factors.…”
Section: Regulators Failed To Safeguard Financial Stabilitymentioning
confidence: 99%
“…The SEC's Associate Director of Trading and Markets, Michael Macchiaroli (2009) emphasized that "the Commission did not relax any requirements at the holding company level because previously there had been no requirements." 2 The extreme leverage of the five investment banks, the existential crises faced by all of them in 2008, and the big post-crisis drop in leverage of the two survivors (Goldman Sachs and Morgan Stanley), all support a view that the SEC had not supervised the investment banks (or their subsidiaries) adequately from the viewpoint of solvency. The Inspector General of the Securities and Exchange Commission (2008) found that the SEC's Division of Trading and Markets "became aware of numerous potential red flags prior to Bear Stearns' collapse [in March 2007], regarding its concentration of mortgage securities, high leverage, shortcomings of risk management in mortgage-backed securities and lack of compliance with the spirit of certain Basel II standards, but did not take actions to limit these risk factors.…”
Section: Regulators Failed To Safeguard Financial Stabilitymentioning
confidence: 99%
“…Network strategies have also been largely applied in research on financial intermediation. Jackson and Pernoud (2020) provide an overview of the relationship between financial networks and systemic risks.…”
Section: Credit Scoring Using Ai/ml and Alternative Datamentioning
confidence: 99%
“…Indeed, eight years after the passage of Dodd-Frank, and nearly a decade after the banking agencies began to work on stronger capital and liquidity regulation, the new regulatory framework in place is still not completed, with numerous proposed regulations not having been finalized. 5 Dodd-Frank affords substantial discretion to the regulatory agencies. The merit of this approach is that it allows for a more finely tuned and informed regulatory implementation.…”
Section: A First Risk: Degradation Of the Resiliency Of Large Bankingmentioning
confidence: 99%